2019
DOI: 10.1016/j.ccell.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Sarcomas Develop through Distinct Evolutionary Pathways

Abstract: SummaryUndifferentiated sarcomas (USARCs) of adults are diverse, rare, and aggressive soft tissue cancers. Recent sequencing efforts have confirmed that USARCs exhibit one of the highest burdens of structural aberrations across human cancer. Here, we sought to unravel the molecular basis of the structural complexity in USARCs by integrating DNA sequencing, ploidy analysis, gene expression, and methylation profiling. We identified whole genome duplication as a prevalent and pernicious force in USARC tumorigenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 57 publications
(89 reference statements)
2
82
0
Order By: Relevance
“…Currently, SigProfilerMatrixGenerator supports only classifications of small mutational events (i.e., single base substitutions, doublet base substitutions, and small insertions and deletions) as we have previously demonstrated that these classifications generalize across all types of human cancer [14]. While classifications for large mutational events (e.g., copy-number changes and structural rearrangements) have been explored by us and others [29, 32, 33] such classifications have been restricted to individual cancer types and it is unclear whether they will generalize in a pan-tissue setting.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Currently, SigProfilerMatrixGenerator supports only classifications of small mutational events (i.e., single base substitutions, doublet base substitutions, and small insertions and deletions) as we have previously demonstrated that these classifications generalize across all types of human cancer [14]. While classifications for large mutational events (e.g., copy-number changes and structural rearrangements) have been explored by us and others [29, 32, 33] such classifications have been restricted to individual cancer types and it is unclear whether they will generalize in a pan-tissue setting.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Early transcriptomic studies [8 , 10] have identified a subgroup of inflammatory MFH/UPS, corroborated by most recent studies, albeit non-specifically dedicated to UPS. [11 , 24] Together, these data bring light to modest results obtained with checkpoint inhibitors in unselected STS patients to date. The PEMBROSARC study assessing pembrolizumab and metronomic cyclophosphamide has reported negative results in unselected STS.…”
Section: Discussionmentioning
confidence: 80%
“…who reported significant enrichment for immune-related pathways in a subset of undifferentiated sarcomas (US) characterized by higher mutational burden, as well as another subset of US characterized by a high rearrangement level. [24] Several studies have investigated how underlying genomic alterations may drive the composition of the tumor micro-environnement in solid tumors. Recent publications in other diseases have showed correlation between mutation burden and cytotoxic immune infiltrates, but also association of high level of CNA with low immune infiltrates and worse response to immune checkpoint blockade [19 , 20 , 28 , 29].…”
Section: Discussionmentioning
confidence: 99%
“…There is also emerging evidence that extraction of copy number signatures from a common cancer, such as high grade serous ovarian carcinoma, provides more robust prognostic information than pathological grading or the analysis of single gene mutations [25]. In sarcomas, copy number signatures have proved useful in understanding the evolutionary trajectories of the genomically complex cancers [26]. In a meta-analysis study of >5000 samples of 12 cancer types, some patterns of somatic copy number alterations were associated with reduced expression of cytotoxic immune signatures [27].…”
Section: Bioinformatics Analysis For Multi-omic Profiling Of Mpnstsmentioning
confidence: 99%